Design and development of undercarriage systems for agricultural tractors with replaceable half-tracks - Z. A. Godzhaev; E. V. Ovchinnikov; A. S. Ovcharenko (Аграрная наука Евро-Северо-Востока, 2023)
The need to use such propulsion devices in mobile agricultural power units is substantiated. The relevance of this development based on global trends is shown. The purpose of the research is to develop the design, to evaluate strain-stress state and functional characteristics of undercarriages of agricultural tractors with replaceable half-tracks. An experimental design of the replaceable tracked undercarriage was developed and manufactured, modeling of loading modes was performed, calculations were carried out by the finite element method of the stress-strain state of structural elements according to 6 load schemes – tractor parking on a flat horizontal surface; movement with maximum traction force; parking across a 30° slope for the upper track; parking across a 30° slope for the lower caterpillar; driving into an obstacle with a deviation of 15°; driving over obstacles based on the central rollers. It was determined that the selected structural material, by the above mentioned loading modes ensure the operability of replaceable tracked undercarriage. Calculations were carried out to check the adequacy of the developed mathematical model using field tests in testing ground of FSAC VIM. It was determined that the maximum stress-strain state of the frame structure of a replaceable tracked undercarriage for all types of loading did not exceed 100 MPa. This provides a two-fold margin of safety in terms of fluidity of the structure, taking into account the characteristics of the selected material. In the maximum loaded state - parking across a slope of 30° - the highest stress on the upper track is 161 MPa, which corresponds to a safety margin of 1.45. The deformation of the bearing assembly was no more than 4 mm, which is allowed by the design of the drive assembly and the caterpillar.